Volkslied und Politik im deutsch-ungarischen Vergleich einst und heute - Éva (FILOGI, 2020)
There is hardly any other genre that, although used over and over again, would be as indefinable and as politically charged as the folk song. This is thanks to the numerous and varied historical meanings of the eponymous word “people”. The article tries to show the triple historicity of the origin, recording and interpretation in both traditions.